Financial assessment of the Indian retail sector: understanding the future direction of the industry. (15th September 2021) - Kolte, Ashutosh; Pawar, Avinash; Sangvikar, Balkrishan; Sawant, Prasanna
The retail sector helps to create a place, time, and possession of utilities that have a tremendous impact on the economy and country. The prime objective of this paper is to assess the Indian retail sector towards the future of the industry with an in-depth fundamental analysis of major players in the Indian retail industry. The selected companies are listed in India and have operations spread throughout the country. The companies considered for this analysis include Avenue Supermart, Aditya Birla Fashion and Retail, Future Retail, Trent Retail and VMart Retail in India. This paper utilises data from the last five years and models for financial analysis which take in value and growth pick model, Piotroski F-score, and Altman z-score along with the discounted cash flow valuation and estimated the future of the companies under consideration. The outcome of this paper shows the future aspects of the Indian retail sector which can prove to be a good help for investors and stakeholders. The comparison in various competitors can be observed in the paper and can help investor decisions to be fruitful in the longer run.